KAJIAN REFERENSI AYAT-AYAT AL QUR’AN DALAM SKRIPSI MAHASISWA PENDIDIKAN BIOLOGI FAKULTAS TARBIYAH DAN KEGURUAN UIN AR-RANIRY - Elita Agustina (Biotik, 2015)
The purpose of this research was to figure out the relevancy of the reference used from verses of the Qur'an to the topic of research, the suitability of the placement of the verses of the Qur'an and supporting references in explaining the verses of the Qur'an in the theses of biology education department students. The methods used in this research were documentation and descriptive analytic method. The data were analyzedby using checklist. The results showed that the relevancy between some verses of Al Qur’an with the topic of the research was 66,7%. While the relevancyof the content of some verses of Al Qur’an with the topic/sub topic of discussion was 57,1%. The suitability of placement of some verses of Al Qur’an based on chaptersin the theses was 54,8%. Meanwhile, the suitability of placement of some verses of Al Qur’an based on the topic/subtopic titles was 50%. Based on the availability of supporting references in explaining some verses of Al Qur’an, it was found that there were 40,5% of students had made conclusions based on supporting references. In conclusion,the level of relevancy and suitability of references from some verses of Qur’an to the topic and its placement were catagorized in the level of appropriate, less appropriate, and inappropriate.